PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER DISERTAI KUIS TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMP SEMEN PADANG Veza Desvita - Desvita, Veza; Aima, Zulfitri; Yuliana Fitri, Dewi (STKIP PGRI Sumbar, 2014)
ABSTRACTThe background of this research was the studentsâ comprehension of mathematic concept still low and the students did not want to ask about the materials that they have not comprehend yet, it could be seen from the result of the second daily test mathematic students at seventh grade of junior high school Semen Padang in year 2013/2014 The kind of this research was experimental research and the design of this research was randomly towards the subject The instrumentation of this research was the comprehension of mathematic concept test Based on the hypothesis test obtained t-table score = 1,67 and t-value= 4,47 because tvalue > ttable, so the hypothesis that the researcher used is accepted which was the believable level was 95 percent. The conclusion of this research was the studentsâ comprehension of mathematic concept that can using the cooperative learning that type Numbered Heads Together that using quiz was better than studentsâ comprehension of mathematic concept that using conventional learning at seventh grade of Junior High School Semen Padang.